Penerapan Pembelajaran Pendidikan Agama Islam Dalam Membentuk Karakter Pribadi Islami Pada Siswa - Al-Muklis; Jannah, Nur (Yayasan Darusssalam Bengkulu, 2024)
This study discusses the application of Islamic religious education as an effort to form the personality of Muslim students who are Islamic. The type of research used is qualitative research. The research approach uses interdisciplinary, including: management, pedagogical, sociological, and psychological approaches. The primary data source of this study is Islamic Religious Education teachers. Secondary data sources in this study are school profile data, theories about the concept of learning strategies, Islamic religious education theories, and theories of Muslim personality formation. Data collection techniques use observation, interviews, and documentation. Data analysis techniques use the stages of data reduction, data presentation, and drawing conclusions. The results of the study found that the Islamic Religious Education learning strategy in forming the personality of Muslim students uses two learning strategies, namely direct learning and indirect learning.